2007
DOI: 10.1086/518786
|View full text |Cite
|
Sign up to set email alerts
|

A Floor in the Solar Wind Magnetic Field

Abstract: Long-term (∼130 years) reconstruction of the interplanetary magnetic field (IMF) based on geomagnetic indices indicates that the solar wind magnetic field strength has a "floor," a baseline value in annual averages that it approaches at each 11 yr solar minimum. In the ecliptic plane at 1 AU, the IMF floor is ∼4.6 nT, a value substantiated by direct solar wind measurements and cosmogenic nuclei data. At high heliolatitudes, Ulysses measured a constant radial field with a magnitude (normalized to 1 AU) of ∼3.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 31 publications
4
87
4
Order By: Relevance
“…Arnab Choudhuri: In our paper of 2007(Jiang et al, MNRAS, 381, 1527 we made some effort to use the polar faculae as a proxy for the next activity cycle. We found two outliers.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Arnab Choudhuri: In our paper of 2007(Jiang et al, MNRAS, 381, 1527 we made some effort to use the polar faculae as a proxy for the next activity cycle. We found two outliers.…”
Section: Discussionmentioning
confidence: 99%
“…2. Cliver and Ling therefore suggested that the floor had a value of ∼2.8 nT, significantly below the Svalgaard et al (2007) value of ∼4.6 nT and also under Crooker and Owens' revised value of ∼3.7 nT. The reduced floor value of 2.8 nT has several advantages.…”
Section: Precursor Relations and The Floormentioning
confidence: 98%
See 3 more Smart Citations